Phase 1, Single‐ and Multiple‐Ascending‐Dose, Food‐Effect, and East Asian Subject Studies to Assess the Pharmacokinetics, Safety, and Tolerability of Bempedoic Acid, a Selective Inhibitor of Adenosine Triphosphate Citrate Lyase - Amore, Benny M.; MacDougall, Diane E.; Hanselman, Jeffrey C.; Emery, Maurice G. (Clinical pharmacology in drug development, 2023)
Bempedoic acid is an adenosine triphosphate citrate lyase inhibitor that lowers low‐density lipoprotein cholesterol by inhibiting cholesterol synthesis and upregulating hepatic low‐density lipoprotein receptor expression. After oral dosing, bempedoic acid was readily absorbed, attaining maximum concentrations with a median time of 3.5 hours, and may be taken without regard to food. Steady‐state oral pharmacokinetics in healthy adults receiving bempedoic acid at the approved 180 mg/day dose were characterized by mean maximum concentration of 20.6 µg/mL, area under the concentration–time curve over 24 hours of 289 µg·h/mL, and elimination half‐life of 21.1 hours. Multiple‐dose pharmacokinetics were linear at bempedoic acid doses of 120–220 mg/day. Circulating concentrations of the active metabolite ESP15228 were 18.0% of bempedoic acid concentrations on average. Comparisons of bempedoic acid 180 mg/day pharmacokinetics after single and multiple dosing revealed no clinically meaningful differences between Japanese, Chinese, and Western subjects. Mean estimates of bempedoic acid elimination half‐life in Japanese (25.2 hours) and Chinese (20.0 hours) subjects were comparable to Western subjects (23.9 hours) following 14 days of once‐daily dosing. Bempedoic acid was generally safe and well tolerated up to a dose of 220 mg/day across the study populations described herein.